Spatial and temporal trends of cervical cancer, Uganda, 2012-2021: A descriptive analysis of surveillance data - Rose Nampeera; Miriam Nakanwagi; Edirisa Junior Nsubuga; Lilian Bulage; Vivian Ntono; Benon Kwesiga; Daniel Kadobera; Nixon Niyonzima; Alex Riolexus Ario (Journal of Interventional Epidemiology and Public Health)
Introduction: Cervical cancer is the leading cause of cancer-related deaths among women in Uganda. The Uganda Ministry of Health (MoH) has adopted a number of strategies to address the burden of cervical cancer, including cervical cancer screening in public health facilities. However, the impact of these interventions on cervical cancer incidence is not documented. We described the spatial and temporal trends of cervical cancer screening and incidence among women attending health facilities in Uganda from 2017 to 2021. Methods: We extracted surveillance data for screening and incident cervical cancer cases per month during 2017-2021 by district, region and country. We calculated the screening and incidence rate by district, region and country level using the Uganda Bureau of Statistics population projections of total female population aged 15+ years as the denominator. We calculated significance of the trends over time using logistic regression. Results: A total of 439,230 women were screened for cervical cancer from 2017 to 2021. The highest screening rate was in 2020 (1,420/100,000) and the lowest was in 2017 (18/100,000). There was a 2.4% increase in the screening rate from 2017 to 2021. Nationwide, 7,073 newly diagnosed cervical cancer cases were observed from 2017 to 2021.The peak incidence of cervical cancer was 1,978 (18/100,000) in 2017 and the lowest incidence was 1,143 (5/100,000) in 2021. There was an overall 3% decrease in incidence of cervical cancer from 18/100,000 in 2017 to 5/100,000 in 2021 (p<0.001). Regionally, there was a significant decrease in the incidence of cervical cancer over the years. Northern Uganda had the least decline of 9%. Eastern Uganda had the biggest decrease of 25% over the years. Conclusion: Despite the significant increase in cervical cancer screening, fewer cases of cervical cancer was registered in Uganda over the years. Only Northern Uganda had an increase in incidence of cervical cancer over the years. We recommend expansion of screening to cover all eligible female populations and strengthening of strategies to sustain the decline in cervical cancer cases. Further investigations are needed to understand the reasons for the increasing incidence in Northern Uganda.